2013
DOI: 10.1002/chem.201204056
|View full text |Cite
|
Sign up to set email alerts
|

Traceless Chelation‐Controlled Rhodium‐Catalyzed Intermolecular Alkene and Alkyne Hydroacylation

Abstract: A new functional-group tolerant, rhodium-catalyzed, sulfide-reduction process is combined with rhodium-catalyzed chelation-controlled hydroacylation reactions to give a traceless hydroacylation protocol. Aryl- and alkenyl aldehydes can be combined with both alkenes, alkynes and allenes to give traceless products in high yields. A preliminary mechanistic proposal is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 65 publications
(58 reference statements)
2
17
0
Order By: Relevance
“…[5] Importantly,this proposed ligand-controlled pathway would also avoid the need for an additional directing group on the aryl ring of the substrate. [6] To initiate our studies,w es creened as mall number of iridium complexes with large/large and large/small ligand pairs.U sing 2-naphthaldehyde (1)a samodel substrate,w e first examined the large/large ligand partnership,u sing precatalysts of the type [(COD)Ir(L 1 )(L 2 )]PF 6 ,w hich are commonly used in ortho-directed aryl labeling (Scheme 2). [2i, 7] In accordance with earlier stoichiometric tritiation work, [3a,b] the use of Crabtreesc atalyst (2) [8] led to appreciable levels of labeling across both the aromatic and formyl positions.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…[5] Importantly,this proposed ligand-controlled pathway would also avoid the need for an additional directing group on the aryl ring of the substrate. [6] To initiate our studies,w es creened as mall number of iridium complexes with large/large and large/small ligand pairs.U sing 2-naphthaldehyde (1)a samodel substrate,w e first examined the large/large ligand partnership,u sing precatalysts of the type [(COD)Ir(L 1 )(L 2 )]PF 6 ,w hich are commonly used in ortho-directed aryl labeling (Scheme 2). [2i, 7] In accordance with earlier stoichiometric tritiation work, [3a,b] the use of Crabtreesc atalyst (2) [8] led to appreciable levels of labeling across both the aromatic and formyl positions.…”
supporting
confidence: 75%
“…We hypothesized, therefore,t hat as maller, cis-enabled ligand pair would facilitate axial aldehyde binding and subsequent formyl CÀHa ctivation (Path B). [6] To initiate our studies,w es creened as mall number of iridium complexes with large/large and large/small ligand pairs.U sing 2-naphthaldehyde (1)a samodel substrate,w e first examined the large/large ligand partnership,u sing precatalysts of the type [(COD)Ir(L 1 )(L 2 )]PF 6 ,w hich are commonly used in ortho-directed aryl labeling (Scheme 2). [6] To initiate our studies,w es creened as mall number of iridium complexes with large/large and large/small ligand pairs.U sing 2-naphthaldehyde (1)a samodel substrate,w e first examined the large/large ligand partnership,u sing precatalysts of the type [(COD)Ir(L 1 )(L 2 )]PF 6 ,w hich are commonly used in ortho-directed aryl labeling (Scheme 2).…”
supporting
confidence: 68%
“…11 Reports of desulfitative alkynylation are rare, and involve activation of the sulfide component, 12 metallated alkynes, 13 or are the result of the coupling of alkynyl thioethers with organometallic reagents. 14 Our laboratory has recently demonstrated that, in combination with a suitable directing group, it is possible to use Rh-bisphosphine complexes to selectively activate the C-S bond of arylmethylsulfides, to effect carbothiolation reactions, 15 reductive desulfurisations, 16 or Suzuki-type cross coupling reactions (Scheme 1). 17 As full selectivity for C-S functionalisation over C-X functionalisation was in each case observed, we envisaged that Scheme 1 Existing C-S activation methodologies and proposed chemoselective Sonogashira-type coupling.…”
mentioning
confidence: 99%
“…We hypothesized, therefore, that a smaller, cis ‐enabled ligand pair would facilitate axial aldehyde binding and subsequent formyl C−H activation (Path B) . Importantly, this proposed ligand‐controlled pathway would also avoid the need for an additional directing group on the aryl ring of the substrate …”
Section: Methodsmentioning
confidence: 91%